The Ethnobotanical and therapeutic application of plants with the altitudinal description of Lar Sadin and Bar Amadak, Tehsil Salarzai, Bajaur, Pakistan - Ahmad, Sajjad; Ghulam Dastagir (Ethnobotany Research and Applications, 2023)
Background: The ethnobotanical and ethnopharmacological studies of an area provide the best possible pathway to conventional modern medicine and other conventional. This study was conducted to collect the traditional knowledge about plants from local people and then convey this knowledge to people of world. Methods: The ethnobotanical information was collected through questionnaires, observations and interviews during 2018-2019. The main focus of interviews was to collect information about plants, local names, ethnobotanical uses, plant part uses, diseases treatment, mode of usage and administration. Collected plant specimens with informants were submitted to the Herbarium of University of Peshawar, Pakistan. Quantitative data of the result were analyzed through ethnobotanical indices. Results: The study reported a total of 209 plants of 180 genera and 64 families were utilized by the local people for various indigenous uses. The highest species belonged to Asteraceae with 21 genera and 25 species followed by Poaceae with 16 genera and 18 species. Out of these 209 plants, 152 species were used as medicinal, 48 as fodder species, 32 as fuel species, 25 species as ornamental, 18 species as vegetables, 13 species as fruits and 6 species as food. The selected area plants were medicinally important for stomachic, vermifuge, fevers, cholera, anthelmintic, diabetes, cancer, laxative, antimicrobial, antiviral and antioxidants. Conclusion: The study area has been extensively occupied by medicinal and non-medicinal plants that are being used for significant purposes. This study uncovered the traditional and ethnobotanical knowledge of study area. The unwritten ethnobotanical knowledge of local people about medicinal plants and altitudinal details must be preserved. Keywords: Ethnobotany, Bajaur Salarzai, Afghan border, Medicinal plants, and Informants consensus.